Videtur Quod: On Method in Theology - Baker, Anthony D. (Heythrop journal, 2023)
Theological language has always faced a fundamental dilemma: it seeks to put the divine reality into limited human language. While this dilemma can obfuscate our theological pathways, it can also generate a new awareness of the task and possibilities of the discipline. New testimonials, or uniquely accented human experiential utterances, have emerged in theological discourse in the past decades, greatly increasing our vision of the expansiveness of theology. The tools for integration into systematic or discursive development are still, however, lacking. This article suggests that an extension of the innovative methodology of Thomas Aquinas, beginning and ending with ‘what seems’ to be the case, putting testimony into discursive forms, and testing for a fittingness with the mysterious and excessive mystery of the divine reality, offers a promising path for discerning common and trustworthy theological language.